2017
DOI: 10.1186/s13643-017-0554-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of person- and family-centered care transition interventions: a systematic review protocol

Abstract: BackgroundCare transitions from the hospital to home are critical to the sustainability of our health care system. Ineffective care transitions can be caused by high incidences of post-discharge adverse events, by poor communication with patients, and/or by inadequate information transfer between providers from the hospital to home. Any one of these can lead to fragmented care, high readmission rates, increased visits to the emergency department, and ultimately poor patient outcomes. Despite the ongoing improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…This was done by grouping similar response statements, and then theming them. To identify any missing themes, the research assistant reviewed the themes against the existing relevant literature found in our recent systematic review on the effectiveness of PFCC transition interventions from hospital to home[35]. Missing themes were then added to the primary data collected during Round 1.…”
Section: Methodsmentioning
confidence: 99%
“…This was done by grouping similar response statements, and then theming them. To identify any missing themes, the research assistant reviewed the themes against the existing relevant literature found in our recent systematic review on the effectiveness of PFCC transition interventions from hospital to home[35]. Missing themes were then added to the primary data collected during Round 1.…”
Section: Methodsmentioning
confidence: 99%
“…Challenges associated with care transitions are complex and thus require a multifaceted approach and coordinated care to improve quality and health outcomes 7,8. Ensuring a high level of person- and family-centered care (PFCC) is one particularly important aspect for improving quality and health outcomes during care transitions 911…”
Section: Introductionmentioning
confidence: 99%
“…The concept of FCC is often poorly characterized and imprecisely described, and the rigor of the research that has studied the concept has been variable (Backman et al, 2017; Kuo et al, 2012; Shields, 2011; Sidani and Fox, 2014). Without conceptual clarity, many of the claims that have been made about the benefits, or otherwise, of FCC lack a solid foundation (Carter, 2008; Uniacke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%